LEVEL OF DIGITALIZATION OF INDONESIAN LOCAL GOVERNMENT THROUGH LITERATURE REVIEW: CASE STUDIES OF SAMARINDA CITY AND BALIKPAPAN CITY - Akbar, Paisal; Nurmandi, Achmad; Mutiarin, Dyah; Jubba, Hasse; Usman, Sunyoto (CosmoGov: Jurnal Ilmu Pemerintahan, 2024)
Digital technology has become a certainty in the government development agenda. Currently, the presence of digital government is considered the final point of achievement in e-government development. So far, many digital government development initiatives have been carried out at the local government level. Still, there has not been any research that examines the extent to which digital government development has been carried out at the district/city level using a variable approach to the digital government evolution classification. This research is to fill the void. This research uses secondary data from literature publications of scientific articles related to digital government in the two cities, namely Samarinda City and Balikpapan City. The search for data related to digital government uses the Google Scholar database as a data source. The data search stage is carried out using the Publish or Perish software to classify the resulting publications based on the theme's relevance. Research findings show an increasing research trend and continue to fluctuate every year. The focus of the issues and dominant themes presented have provided new information and understanding regarding how digital governance in the two cities has been implemented so far. Furthermore, the findings of this study also show that, in general, the level of evolution of digital government in both towns in Samarinda City and Balikpapan City has existed in the four available evolutionary stages. Still, some steps are dominant, and others are not dominant.gb777